Elucidation of hole transport mechanism in efficient energy cascade organic photovoltaics using triple donor system - Jung, Kwanwook; Park, Soohyung; Yoo, Jisu; Jung, Na Eun; Moon, Byung Joon; Lee, Sang Hyun; Yi, Yeonjin; Lee, Hyunbok (Elsevier BV, 2022)
Recently, the energy cascade structure using multiple light-absorbing layers has been considered as a novel device architecture to overcome the inherent limitations of small-molecule organic photovoltaics (OPVs). The light-absorbing layers in the energy cascade OPVs should have a large overlap between the emission spectrum of a Fo center dot rster resonance energy transfer (FRET) donor and absorption spectrum of a FRET acceptor. An equally important requirement is efficient charge transport across the organic layers by the formation of a suitable energy-level alignment. 5,10,15,20-tetraphenylbisbenz[5,6]indeno[1,2,3-cd:1 ',2 ',3 '-lm]perylene (DBP)/ 5,6,11,12-tetraphenyltetracene (RUB)/5,12-diphenyltetracene (DPT) layers are representative donor systems, which exhibited a high power conversion efficiency in energy cascade OPVs. However, the detailed holetransport mechanism has not been understood. In this study, the energy level alignment of C60/DBP/RUB/ DPT/poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) layers was investigated via in-situ ultraviolet photoelectron spectroscopy and inverse photoelectron spectroscopy. The highest-occupied molecular orbital levels of DBP/RUB/DPT were almost perfectly aligned after their contact, indicating an efficient hole transport toward the anode without hindrance of energy barrier after exciton dissociation. This is owing to the formation of an interface dipole that aligns the charge neutrality levels of the organic layers.